GERAKAN BERANI VAKSIN COVID-19 BERSAMA LION AIR GROUP - Sukarno, Anita; Dewi, Ratna; Nurhayati, Ety; Mulyana, Budi; Fatmawati, Kiki Amanda (Jurnal Pengabdian Masyarakat AbdiMas, 2021)
The Covid-19 pandemic has had a negative impact on every aspect of Indonesian life. The Covid-19 vaccine has been created and its distribution has proceeded progressively, especially in Indonesia. The Indonesian government has launched a massive use of the Covid-19 vaccine and it is hoped that approximately 118 million Indonesians have succeeded in getting the vaccine. This is carried out with an effort to create community immunity (herd immunity) in every community in order to break the chain of spread of Covid-19. Lion Air Group is a company engaged in air transportation that demands human movement. In order for this mobilization need to work, the Lion Air Group participates in the success of the Indonesian government's program in eradicating Covid-19 through a vaccination program. Thus, the air transportation mode is no longer a threat to the community so that the circulation of mobilization needs continues. The potential group as the target of this activity is the entire workforce of the Lion Air Group. The method of carrying out the activity is by injecting the Sars-Cov 2 (Sinovac) vaccine with a dose of 0.5 ml in the muscular deltoid area of the left. This activity takes place for 10 days each in March and April 2021 in collaboration with the Ministry of Health and mandated Health Workers. This activity succeeded in targeting 15,733 (Phase 1) and 14,233 (Phase II) participants. Thus, the implementation of the vaccination activity can be a scourge in the creation of herd immunity. Keywords: Covid-19, herd immunity, vaccine